Удосконалення технології масляних паст, стабілізованих білково-полісахаридними комплексами, з мікронутрієнтами чорниці - Яценко, Ольга Володимирівна (My University, 2021)
Дисертаційна робота присвячена удосконаленню технології масляних паст шляхом розробки білково-полісахаридних комплексів на основі молочних та рослинних білків та збагачення продуктів мікронутрієнтами чорниці. Обґрунтовано вибір компонентів та розроблено білково-полісахаридний комплекс на основі казеїнату натрію та молочних білків, визначено їх раціональний вміст у складі нормалізуючого компоненту на знежиреному молоці : казеїнат натрію – 10%, гуарова камедь – 1%; казеїнат натрію – 10%, камедь рожкового дерева – 0,25%; СКМБ-УФ – 10,0%, ТПФ – 1,0%, КСБ-УФ – 3,0%, κ-каррагінан – 0,05%, KCl – 0,002 %, гуарова камідь – 0,3%. Для збільшення економічної ефективності виробництва масляних паст обґрунтовано доцільність використання ізоляту білка гороху в кількості 2,5% від маси продукту. Обґрунтовано спосіб введення та визначено технологічні параметри підготовки порошку ягід чорниці – після гідратації на знежиреному молоці за співвідношення 1:7, температура процесу – (40±5) ºС, тривалість 10-15 хв. та визначений раціональний вміст порошку чорниці у масляній пасті – 3…5 % . Розроблено рецептурний та визначено технологічні параметри виробництва масляних паст за рекомбінантною схемою, що дозволить розширити можливості підприємств у випуску асортименту масляних паст, забезпечить отримання продукту однорідного складу та стабільної якості. Обґрунтовано гарантійний термін зберігання нових видів масляних паст: за температури (4±2)°С ‒ не більше 7 діб, мінус (3±1)°С - не більше 15 діб, мінус (24±2) ‒ не більше 30 діб. The thesis is devoted to the improvement of butter paste technology by developing protein-polysaccharide complexes based on dairy and vegetable proteins, which provide the formation of the product structure as a low-calorie analogue of butter, increase the nutritional value of the product by enriching it with high protein digestibility. The introduction of new types of butter pastes of bilberry micronutrients enriches the product with a complex of biologically active compounds. In order to increase the efficiency of stabilization complexes and the formation of consumer properties of butter pastes, the choice of components is substantiated and a protein-polysaccharide complex based on milk proteins is developed, their rational content in the composition of the normalizing component in skim milk: sodium caseinate – 10,0%, guar gum – 1,0%; sodium caseinate – 10,0%, carob gum – 0,25%; milk protein concentrate (UF) – 10,0%, sodium tripolyphosphate – 1,0%, whey protein concentrate (UF) – 3,0%, κ-carrageenan – 0,05%, potassium chloride – 0,002%, guar gum – 0,3%, which will purposefully form the structure of butter paste as a low-calorie analogue butter and enrich the product with complete protein. To increase the economic efficiency of butter paste production, the expediency of using pea protein isolate in the amount of 2,5% by weight of the product is substantiated. Technological parameters of preparation of vegetable protein isolates are determined: hydration on skim milk for 24 hours at temperature (6 ± 2) ° С (ratio 1: 6) followed by heat treatment at a temperature of (82 ± 2) ° С, and keeping for 10… 15 minutes and cooling to (20 ± 2) ° C. The greatest increase in enthalpy occurs when introduced into the system, which is due to the formation of a strong framework of kappa-casein - carrageenan. The enthalpy of the butter paste is slightly higher than that of butter, due to the additional moisture binding of the butter to the components of the stabilization system. Thus, the butter paste produced using the developed protein-polysaccharide complex is a fairly thermodynamically stable system that will ensure the stability of product quality during storage. The microstructure of butter pastes stabilized by protein-polysaccharide complexes based on milk and vegetable proteins has been studied, which proves the effect of interaction of compound formulations with the formation of a single spatial grid, which, unlike butter, is formed by gels of macromolecular lipophilic-hydrophilic hydrophilic compounds. The use of freeze-dried bilberry powder in the technology of butter pastes was substantiated. The selection criteria were: availability on the Ukrainian market, seasonality compensation and minimal losses of biologically active components of berry raw materials during its processing, high consumer rating of butter paste with bilberry micronutrients. The method of introduction was substantiated and the technological parameters of bilberry berry powder preparation were determined - after hydration on skim milk at a ratio of 1: 7, process temperature – (40 ± 5) ºС, duration 10-15 min; determined rational content of bilberry powder in butter paste – 3…5%. The recipe composition of butter pastes stabilized by protein-polysaccharide complexes based on milk proteins, milk proteins and pea protein isolate enriched with bilberry micronutrients has been developed.
Keywords: мікронутрієнти чорниці; масляна паста; білково-полісахаридний комплекс; bilberry micronutrients; butter paste; protein-polysaccharide complex